Tinjauan ‘Urf terhadap Denda Akibat Pembatalan Batando (Studi di Nagari Taeh Bukik Kabupaten Lima Puluh Kota) - Ulvia Bunga Lestari; Dahyul Daipon (Lembaga Yasin AlSys, 2026)
Although the practice of fines due to the cancellation of batando in Minangkabau society has received attention in studies of customary law and Islamic law, research that specifically analyzes the implementation of fines for the cancellation of batando in Nagari Taeh Bukik from the perspective of ‘urf remains limited. This study aims to analyze the implementation of fines resulting from the cancellation of batando and to assess their conformity with the concept of ‘urf in Islamic law. This study used a qualitative approach with a case study design. The research participants consisted of ninik mamak, customary leaders, community leaders, and parties who had been involved in the cancellation of batando, selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, then analyzed using an interactive analysis model comprising data reduction, data display, and conclusion drawing. The results show that a customary fine of five units of gold is imposed on the party who cancels the batando based on the agreement of the parties from the beginning of the proposal procession. The implementation of this fine aims to maintain family honor, strengthen responsibility, and prevent social conflict. Viewed from the perspective of ‘urf, this practice is a custom that lives within the community and can be accepted as long as it fulfills the principles of public benefit, justice, and does not contradict Islamic law. The conclusion of this study affirms that fines for the cancellation of batando can be understood as a customary mechanism that functions to maintain social harmony while also having relevance to the principles of Islamic law. The implications of this study include theoretical contributions to the development of Islamic family law studies, particularly regarding the relationship between Minangkabau customary law and the concept of ‘urf, as well as practical implications for customary communities and policymakers in resolving proposal disputes fairly, beneficially, and in accordance with the values of Islamic law.